2008
DOI: 10.1007/s00420-008-0317-1
|View full text |Cite
|
Sign up to set email alerts
|

Noise induced hearing loss and other hearing complaints among musicians of symphony orchestras

Abstract: Objectives An investigation of the hearing status of musicians of professional symphony orchestras. Main questions are: (1) Should musicians be treated as a special group with regard to hearing, noise, and noise related hearing problems (2) Do patterns of hearing damage diVer for diVerent instrument types (3) Do OAE have an added value in the diagnosis of noise induced hearing loss (NIHL) in musicians. Methods 241 professional musicians, aged between 23-64 participated. A brief medical history and the subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
117
2
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(146 citation statements)
references
References 24 publications
7
117
2
15
Order By: Relevance
“…In a study with 329 music students (aged between 18 and 25 years), there was no evidence of hearing loss, but of acoustic notch in 45% of the students (78% of them presented acoustic notch in 6,000 Hz and 22% in 4,000 Hz) (17) . Other studies also found hearing disorders among musicians, but not at high proportions; however, they observed acoustic notch in the frequencies of 4,000 or 6,000 Hz, more often than expected when compared to non-musicians, considering the same age and gender (1,3,8,9,(18)(19)(20) . It was observed that hearing thresholds of musicians got worse with time of exposure to music and, in this assessed group, the longer the time of exposure (in years), the worse the hearing thresholds found in high-frequency audiometry (Table 1).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In a study with 329 music students (aged between 18 and 25 years), there was no evidence of hearing loss, but of acoustic notch in 45% of the students (78% of them presented acoustic notch in 6,000 Hz and 22% in 4,000 Hz) (17) . Other studies also found hearing disorders among musicians, but not at high proportions; however, they observed acoustic notch in the frequencies of 4,000 or 6,000 Hz, more often than expected when compared to non-musicians, considering the same age and gender (1,3,8,9,(18)(19)(20) . It was observed that hearing thresholds of musicians got worse with time of exposure to music and, in this assessed group, the longer the time of exposure (in years), the worse the hearing thresholds found in high-frequency audiometry (Table 1).…”
Section: Discussionmentioning
confidence: 86%
“…Researchers throughout the world described hearing disorders caused by exposure to music, such as hearing impairment or differences in hearing thresholds, not necessarily as disorders related to hearing loss, especially in high frequencies (3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the frequency of the complaint tinnitus ranged from 37.5% to 45%, and the complaint intolerance to loud sound ranged from 19% to 48%. 4,[6][7][8]14,16,[22][23][24][25] The same complaints were also reported after shows; tinnitus in this situation may be related to a temporary change in hearing thresholds as a result of exposure to highly amplified music, even for short time periods. It should be noted that the average daily exposure was three hours and the average weekly exposure was ten hours, which are lower than a regular workday (8h/day or 40h/ week).…”
Section: Discussionmentioning
confidence: 84%
“…Because hearing loss caused by high sound pressure levels starts with outer hair cell damage, [27][28][29][30][31] OAE may be more sensitive than pure tone audiometry to detect early changes due to exposure to amplified music. 4,7,16,25,26,31 Responses in the questionnaire on satisfaction with the HiFi ER 20 hearing protector were concentrated in the "agree" and "fully agree" groups, indicating a positive attitude towards using hearing protectors. Two questions were exceptions: clear perception of high frequency sounds, and full-time use of the ER 20 hearing protector during shows.…”
Section: Discussionmentioning
confidence: 99%